(untitled) (International Journal of Innovative Technologies in Economy, 2018)
The article is devoted to the study of the concept of compromising the personal key of digital signature, the legal aspects of compromise in the context of the theory of law. The paper presents the concept of explicit and implicit compromise and the limits of their actions, as well as the legal consequences of compromise.